2019
DOI: 10.3389/fimmu.2019.01361
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Effects of Acute and Prolonged Interleukin 33 Exposure on Mast Cell IgE-Mediated Functions

Abstract: Background: Epithelial cytokines, including IL-33 and Thymic stromal lymphopoietin (TSLP), have attracted interest because of their roles in chronic allergic inflammation-related conditions such as asthma. Mast cells are one of the major targets of IL-33, to which they respond by secreting cytokines. Most studies performed thus far have investigated the acute effects of IL-33 on mast cells. In the current study, we investigated how acute vs. prolonged exposure of mast cells to IL-33 and TSLP affects… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 43 publications
4
33
0
Order By: Relevance
“…In addition, MC were detected in the synovial fluid in a higher proportion of SpA patients compared to patients with other forms of arthritis 66 . Similarly to our observations in mice, a promoting effect of IL-33 on GM-CSF secretion by human MC has been reported in several studies 48,67 , supporting the potential relevance of the MC-mediated IL-33/ GM-CSF axis to the inflammatory response to humans. Consequently, MCs may represent a promising therapeutic target for SpA, with a recent pilot study suggesting this approach could be safe and effective 68 .…”
Section: Discussionsupporting
confidence: 91%
“…In addition, MC were detected in the synovial fluid in a higher proportion of SpA patients compared to patients with other forms of arthritis 66 . Similarly to our observations in mice, a promoting effect of IL-33 on GM-CSF secretion by human MC has been reported in several studies 48,67 , supporting the potential relevance of the MC-mediated IL-33/ GM-CSF axis to the inflammatory response to humans. Consequently, MCs may represent a promising therapeutic target for SpA, with a recent pilot study suggesting this approach could be safe and effective 68 .…”
Section: Discussionsupporting
confidence: 91%
“…Han et al described an antiapoptotic effect in the human MC line (HMC)-1 (as well as in the immature murine bone marrow-derived mast cell (BMMC) [27], while human lung MCs did not experience survival promotion by TSLP [25]. Together, this indicates that immaturity and/or malignant transformation may have pre-disposed to survival rescue by TSLP, which is also in accordance with a recent finding of increased TSLPR expression in the continuously growing MC line ROSA vis-à-vis primary MCs [28]. However, because skin MCs, not studied previously, represent primary, fully differentiated MCs, just like lung MCs, our current data instead imply that MCs at a post-maturation stage are amenable to survival protection by TSLP and that the microenvironment in which they completed maturation will primarily dictate this response.…”
Section: Discussionsupporting
confidence: 75%
“…TSLP notably contributes to skin disorders like AD [20,54], and accordingly, binding to its specific receptor has been reported to regulate selected aspects of MC biology, including maturation and mediator secretion [24,25,26,27]. In this regard, Lai et al demonstrated that TSLP can increase Tryptase storage [55], whereas Rönnberg et al showed an opposite effect [28], underlining the heterogeneous character of MCs. Han et al described an antiapoptotic effect in the human MC line (HMC)-1 (as well as in the immature murine bone marrow-derived mast cell (BMMC) [27], while human lung MCs did not experience survival promotion by TSLP [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that IL33-elicited responses in MCs differ from IgE stimulation and that IL33-mediated responses in MCs are modified, and often potentiated, when secondary stimuli like IgE, substance P or IL3 are present (112,(141)(142)(143)(144). Further research is required to uncover other MC-activating factors present in the tumor microenvironment and how they impact IL33 signaling and MC activation.…”
Section: Diversity Of Mast Cell Activation Signalsmentioning
confidence: 99%